Diagnosis and Treatment of Myeloproliferative Neoplasms With PCM1-JAK2 Rearrangement: Case Report and Literature Review - Sun, Yingxin; Cai, Yifeng; Chen, Jia; Cen, Jiannong; Zhu, Mingqing; Pan, Jinlan; Wu, Depei; Sun, Aining; Chen, Suning (Frontiers in Oncology, 2021)
Myeloproliferative neoplasms (MPN) with PCM1-JAK2 rearrangement is rare disease with poor prognosis and lacks of uniform treatment guidelines. Several studies confirmed the efficacy of ruxolitinib in hematological malignancies with PCM1-JAK2 fusion, but the efficacy is variable. Here, we report two patients diagnosed with MPN with PCM1-JAK2 fusion, who were treated with ruxolitinib-based regimen, including the first case of ruxolitinib combined with pegylated interferon (Peg-IFN), and conduct a literature review. We found that ruxolitinib combined with Peg-IFN is an effective treatment option in the case of poor efficacy of ruxolitinib monotherapy.